2006
DOI: 10.4049/jimmunol.177.7.4558
|View full text |Cite
|
Sign up to set email alerts
|

CD25+CD4+ Regulatory T Cells and Memory T Cells Prevent Lymphopenia-Induced Proliferation of Naive T Cells in Transient States of Lymphopenia

Abstract: Lymphopenia has been associated with autoimmune pathology and it has been suggested that lymphopenia-induced proliferation of naive T cells may be responsible for the development of immune pathology. In this study we demonstrate that lymphopenia-induced proliferation is restricted to conditions of extreme lymphopenia, because neither naive nor memory T cells transferred into T cell-depleted hosts proliferate unless the depletion exceeds 90% of the peripheral repertoire. Memory CD4 T cells as well as regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 71 publications
6
44
0
1
Order By: Relevance
“…It has been postulated that they are neutral 'bystanders' , meaning that they do not contribute nor impair immune responses. It has also been suggested that they may down-regulate the immune response by suppressing the proliferation of naive T cells through a mechanism that mirrors the suppression of naive T cells by memory T cells [61]. Alternatively, it has also been reported that antigen-independent proliferating CD8 + T cells enhance the immune response through production of IFN-γ and other mediators of effector functions [19,51,62].…”
Section: Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that they are neutral 'bystanders' , meaning that they do not contribute nor impair immune responses. It has also been suggested that they may down-regulate the immune response by suppressing the proliferation of naive T cells through a mechanism that mirrors the suppression of naive T cells by memory T cells [61]. Alternatively, it has also been reported that antigen-independent proliferating CD8 + T cells enhance the immune response through production of IFN-γ and other mediators of effector functions [19,51,62].…”
Section: Cd8mentioning
confidence: 99%
“…Quantification of A/PR8 influenza virus using real-time PCR was performed as described previously [61]. Briefly, total RNA was extracted from aliquots of lung homogenates using a QIAamp Viral RNA Kit (Qiagen).…”
Section: Viral Titre Determination By Quantitative Reverse Transcriptmentioning
confidence: 99%
“…Although previous reports show absence of CD4 1 T cells in early reconstitution after CB HSCT, 54 others suggest the presence of residual donor T cells including Treg cells after HSCT depending on the conditioning used. [56][57][58] These studies highlighted the survival of Treg cells and the possibility that these cells create a tolerant environment that may have an impact on NK cells which is crucial for early responses after HSCT.…”
Section: Interaction Between Nk Cells and Treg Cells In Hematopoieticmentioning
confidence: 99%
“…However, these data gathered with various experimental methods are difficult to combine into a single model accounting for the quantitative aspects of cell dynamics. In addition, the temporal parameters of the population dynamics of T cells in response to a short lymphopenia have only partially been established (22)(23)(24)(25)(26). This leaves us with a puzzling, complex, and incomplete view of thymocyte and peripheral T cell dynamics.…”
mentioning
confidence: 99%